Unveiling the rat urinary proteome with three complementary proteomics approaches. Issue 17 (2nd September 2013) - Sánchez‐Juanes, Fernando; Muñiz, María Carmen; Raposo, César; Rodríguez‐Prieto, Silvia; Paradela, Alberto; Quiros, Yaremi; López‐Hernández, Francisco; González‐Buitrago, José Manuel; Ferreira, Laura
<x xml:space="preserve">Abstract</x> Urine is a suitable biological fluid to look for markers of physiological and pathological processes, including renal and nonrenal diseases. In addition, it is an optimal body sample for diagnosis, because it is easily obtained without invasive procedures and can be sampled in large quantities at almost any time. Rats are frequently used as a model to study human diseases, and rat urine has been analyzed to search for disease biomarkers. The normal human urinary proteome has been studied extensively, but the normal rat urinary proteome has not been studied in such depth. In light of this, we were prompted to analyze the normal rat urinary proteome using three complementary proteomics platforms: SDS‐PAGE separation, followed by LC‐ESI‐MS/MS; 2DE, followed by MALDI‐TOF‐TOF and 2D‐liquid chromatography‐chromatofocusing, followed by LC‐ESI‐Q‐TOF. A total of 366 unique proteins were identified, of which only 5.2% of unique proteins were identified jointly by the three proteomics platforms used. This suggests that simultaneous proteomics techniques provide complementary and nonredundant information. Our analysis affords the most extensive rat urinary protein database currently available and this may be useful in the study of renal physiology and in the search for biomarkers related to renal and nonrenal diseases.